(Nitrito-κ2O:O′)bis[tris(4-fluorophenyl)phosphine-κP]silver(I) - Frederick P. Malan; Kariska Potgieter; Reinout Meijboom (IUCrData)
The molecular structure of the title AgI complex, [Ag(NO2)(C18H12F3P)2], features a distorted tetrahedral geometry about the central AgI atom, with a total range of bond angles spanning from 49.80 (5) to 114.92 (1)°. The distortion arises primarily due to the small bite angle [49.80 (5)°] of the nitrito ligand. The compound crystallizes with one molecule in the asymmetric unit, in the space group P21/n, with Z = 4 and Z′ = 1.